Situational materialism: an extension and replication - Watson, David; Schmaltz, Rodney (My University, 2023)
Materialistic thoughts have been associated with poorer life-satisfaction, increased incidence of depression, and lowered self-control. Invoking materialistic thoughts seem to impact health behaviours, such as consuming unhealthy snacks. Kim (2013) found that when materialistic thoughts are activated, participants are more likely to engage in unhealthy behaviours, such as increasing consumption of candy. Kim proposed that the mechanism for this behaviour is that materialistic thoughts lower self-control, which then leads to an increase in consumption of unhealthy food. In the current study, the role of envy on self-control, using a similar experimental paradigm as Kim was investigated. Over the course of three studies, replication of the finding that inducing materialistic thoughts has an impact on eating behaviour was unfounded as none of the differences between experimental conditions were significant. Possible explanations for this failure to replicate are presented.
Keywords: materialism; replication study; self-control; envy